High capacity, low pressure hydrogen storage based on magnesium hydride and thermochemical heat storage: Experimental proof of concept. (1st August 2020) - Lutz, Michael; Linder, Marc; Bürger, Inga
Graphical abstract: Highlights: Experimental hydrogen storage and release from a novel adiabatic storage reactor. Coupling of a metal hydride with a thermochemical heat storage material. Magnesium hydride and magnesium hydroxide suitable for hydrogen storage. Magnesium oxide hydration at 9.75 bar results in reactor temperature of 300 °C. Abstract: With hydrogen becoming more and more important as energy carrier, there is a need for high capacity storage technologies preferably operating at low pressures. Chemical storage in metal hydrides is promising for that purpose, but they require thermal management for hydrogen release and storage, respectively. To overcome this challenge, it is beneficial to store the heat needed for hydrogen release during hydrogen storage in the storage system keeping the additional effort to provide that heat low. In this work, the experimental proof of concept of an adiabatic storage reactor is presented. Magnesium hydride and magnesium hydroxide have been used for hydrogen storage and thermochemical heat storage, respectively. A prototype reactor has been developed and experimentally investigated. It was found that the operating temperature of the materials can be adjusted with the gas pressure in a way to establish a temperature gradient from the MgH2 to the Mg(OH)2 and vice versa. Hydrogen storage and release is enhanced by the thermochemical heating/cooling. A pressure of 9 bar is sufficient to store hydrogen with a capacity of 20.8 gH2 L -1 based on the two materials only, without the steel vessel or insulation. In the heat storage compartment, 300 °C have been reached at 9.75 bar during heat release which is high enough to drive the MgH2 dehydrogenation.